2014
DOI: 10.1111/apt.12860
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics, pharmacodynamics and safety of oral doses of ilaprazole 10, 20 and 40 mg and esomeprazole 40 mg in healthy subjects: a randomised, open‐label crossover study

Abstract: SUMMARY BackgroundIlaprazole, a proton pump inhibitor (PPI) currently in clinical use, may provide improved acid suppression vs. other PPIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 17 publications
1
22
0
2
Order By: Relevance
“…; Shin et al. ) as the objective measurement of pH is not known to be prone to placebo effect or subject rating bias.…”
Section: Methodsmentioning
confidence: 99%
“…; Shin et al. ) as the objective measurement of pH is not known to be prone to placebo effect or subject rating bias.…”
Section: Methodsmentioning
confidence: 99%
“…[28][29][30] Accordingly, ilaprazole is expected to have a longer duration of action and less NAB compared to other PPIs. 31,32 But we found that GERD symptoms, 24-hour mean gastric pH, nocturnal mean gastric pH, frequency and duration of NAB, were comparable between the ilaprazole and omeprazole groups. The only significant difference was occurrence of lesser number of NAB episodes in the ilaprazole group.…”
Section: Discussionmentioning
confidence: 68%
“…13 Thus, many physicians from this study also opine that almost half of the patients of APD could be the potential candidates for longer acting PPIs for better symptomatic control. Expert opinion by Bartoli et al highlights that, ilaprazole (10 mg) is better than conventional PPIs like pantoprazole, rabeprazole etc.…”
Section: Discussionmentioning
confidence: 76%